2022
DOI: 10.1002/1873-3468.14557
|View full text |Cite
|
Sign up to set email alerts
|

The TRAPP complexes: discriminating GTPases in context

Abstract: Correct localization of Rab GTPases in cells is critical for proper function in membrane trafficking. Guanine‐nucleotide exchange factors (GEFs) act as the primary determinants of Rab localization by activating and stabilizing their Rab substrates on specific organelle and vesicle membranes. The TRAPP complexes TRAPPII and TRAPPIII are two related GEFs that use the same catalytic site to activate distinct Rabs, Rab11 and Rab1, respectively. The Rab C‐terminal hypervariable domain (HVD) is an important specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…There are two other RabGEFs known to bind directly to the HVDs of their substrates, the TRAPPII and TRAPPIII complexes 26,36,37,47 . The TRAPP complexes use their shared Trs31 subunit to bind to the Rab1 and Rab11 HVDs, also encompassing their CIM motifs, similar to the Rgp1-HVD interaction (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two other RabGEFs known to bind directly to the HVDs of their substrates, the TRAPPII and TRAPPIII complexes 26,36,37,47 . The TRAPP complexes use their shared Trs31 subunit to bind to the Rab1 and Rab11 HVDs, also encompassing their CIM motifs, similar to the Rgp1-HVD interaction (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The HVD has been reported to be important for some, but not all, Rab proteins [61][62][63][64][65] . Structural and functional analysis of the TRAPP complexes revealed that direct interactions with the HVDs of their Rab substrates are important for their substrate specificity 26,36,37,47 . The architecture of the Mon1-Ccz1 GEF complex bound to Rab7 66,67 suggests this GEF may also directly bind to the HVD of its substrate, although an interaction with the Rab7 HVD has not yet been visualized.…”
Section: Discussionmentioning
confidence: 99%
“…This distance was shown to be "measured" by RabGEFs of the TRAPP subfamily to distinguish between related membrane-anchored Rab GTPases ( [35], reviewed in ref. [36]).…”
Section: Membranes Potentiate the Gef Efficiency Through 3d Coinciden...mentioning
confidence: 99%
“…GEFs are generally multidomain proteins with conformational plasticity and often assemble in multisubunit complexes that interact with membranes to activate small GTPases attached to membranes. Galindo and Munro [6] and Bagde and Fromme [5] discuss how combined crystallography, cryo‐electron microscopy, and in vitro reconstitutions uncovered major features of the architecture, mechanism, and specificity of the yeast and metazoan transport protein particle (TRAPP)II and TRAPIII complexes, two related multisubunit GEFs for Rab GTPases, which function in secretion and autophagy. These reviews highlight the critical role of membranes in enforcing the specificities of each TRAPP complex towards a particular set of Rab GTPases, through the combination of specific regulatory subunits, recognition of distinct features of particular Rabs in the context of membranes, and conformational rearrangements.…”
mentioning
confidence: 99%
“…We are now delighted to present 13 articles that highlight how integrated structural, biochemical, and biophysical approaches have allowed to shed light on the mechanisms of fundamental functions of major members of this superfamily. Notably, these reviews show how several experimental approaches that were rarely used a decade ago, are now taking center stage in moving the field forward: reconstitutions of small GTPase systems in artificial membranes [5][6][7][8][9], single particle cryo-electron microscopy [5][6][7][9][10][11][12], 3D electron tomography reconstructions [12], or optogenetics [13]. Of these, Loose and coauthors present a great overview of the power and inherent difficulties of in vitro reconstitutions using biomimetic membranes, and how they have revealed in a quantitative manner the inner workings of intricate small GTPase networks, which would have been unattainable in vivo [8].…”
mentioning
confidence: 99%